IMPLEMENTING ASSESSMENT FOR LEARNING IN THE CHINESE EFL CONTEXT: AN EXPLORATORY ACTION RESEARCH - Zhu, Yan; Pan, Mingwei (UPI Press, 2017)
This article reports on a two-year-long action research project, where Assessment for Learning (AfL) was implemented in a tertiary foreign language classroom in China. It aims to seek answers to three research questions. First, to what extent can AfL impact on learner autonomy? Second, to what extent can AfL effectively improve learners’ proficiency of the target language? Third, what factors may influence the implementation of AfL? The qualitative data elicited from the interviews with learners, triangulated with the quantitative data from questionnaires, revealed that AfL is a rather effective way of promoting learner autonomy. In addition, quantitative data from a pre- and post-test lend support to the hypothesis that AfL in general achieves overall beneficial effects on learners’ language proficiency, though there are differential effects on sub-groups, i.e. female vs. male, and Shanghainese vs. non-Shanghainese. This study also pinpoints certain factors that are possibly conducive to or constraining the implementation of AfL in the Chinese EFL context.